Reimaging Radiation Safety: A Call for Unified Practices in the Digital Imaging Era - Kumar, Abhishek; Angiras, Shivam; Singh, Kushal; Yadav, Santosh Kumar; Mishra, Atul (Indian Journal of Radiology and Imaging, 2025)
Radiation protection is at a crossroads in the era of digital imaging. Although radiographic modalities have made tremendous leaps in diagnostic sensitivity, they have, in turn, added new challenges in guaranteeing proper protection against radiation. Inconsistencies in exposure protocols, lack of health worker awareness, and differing utilization of dose optimization aids still undermine the dictums of justification and ALARA (As Low As Reasonably Achievable). This commentary calls upon the radiology and medical imaging community to embrace a concerted approach to radiation safety, based on international standards and informed by strong education, technology, and policy infrastructures. Such concerted practice has the potential to harmonize safety culture across health care systems and enable imaging professionals to reduce patient and occupational exposure without diminishing diagnostic effectiveness.
Keywords: radiation safety; digital imaging; dose optimization; radiology standards